Experimental investigation on effect of design parameters of encapsulated ice thermal energy storage tanks on cold capacity storage - Turgut, Buket; Erdemir, Dogan; Altuntop, Necdet (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2026)
The design parameters of encapsulated ice thermal energy storage systems significantly influence their overall performance. This study focuses on experimentally investigating the key design characteristics of an encapsulated ice storage tank, a central component in such systems. The porosity within the tank significantly influences both the pressure drop and cold storage capacity. To optimize performance, this study experimentally examines the porosity of tank under different operating conditions by adjusting the number of ice capsules within the storage tank. The experiments involve varying the number of capsules (333, 666, 999, 1332, and 1665) and charging temperatures (-8,-10, and-12 degrees C) to assess their impact on exergy destruction, cold storage capacity, and temperature stratification within the tank. The findings of this study contribute to a deeper understanding of how design parameters affect the performance of encapsulated ice thermal energy storage systems, providing valuable insights for the development of more efficient and effective systems. The comprehensive performance evaluation of the tank encompasses an assessment of its exergy destruction, cold energy storage capacity, and temperature stratification in the tank. The experimental results demonstrate that decreasing the porosity, achieved by adding more capsules, enhances the energy storage capacity of the ice thermal energy storage (ITES) system. Furthermore, a lower inlet temperature of the heat transfer fluid (HTF) improves the quantity of energy stored. However, this lower temperature also increases the HTF's viscosity, which in turn raises the pumping power required. Notably, the scenario with 333 ice capsules and a charging temperature of-12 degrees C exhibits the lowest exergy destruction (599 kJ) and the highest energy storage capacity (5000 kJ).
Keywords: Ice thermal energy storage; Tank porosity; Packed bed configuration; Heat storage; Temperature stratification; Exergy destruction; SYSTEM; PERFORMANCE; EXERGY; BUILDINGS; COST; Thermodynamics; Engineering